2017
DOI: 10.1177/2047487317728765
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of lifelong exercise training on left ventricular function after myocardial infarction

Abstract: Background Endurance exercise training induces cardio-protective effects, but athletes are not exempted from a myocardial infarction. Evidence from animal studies suggests that exercise training attenuates pathological left ventricular remodelling following myocardial infarction. We tested the hypothesis that lifelong exercise training is related to attenuated pathological left ventricular remodelling after myocardial infarction as evidenced by better left ventricular systolic function in veteran athletes comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
0
30
0
2
Order By: Relevance
“…For many years, avoiding physical activity after MI was recommended; however, the current view proposes that moderate exercise training should be a part of cardiac rehabilitation programmes. There is increasing evidence that exercise training, including exercise training before and after infarction, provides promising effects on the repair of the infarcted heart, regardless of the decrease in infarct size and cardiac fibrosis, the attenuation of apoptosis in the myocardium, improvements in ventricular remodelling and inflammation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, avoiding physical activity after MI was recommended; however, the current view proposes that moderate exercise training should be a part of cardiac rehabilitation programmes. There is increasing evidence that exercise training, including exercise training before and after infarction, provides promising effects on the repair of the infarcted heart, regardless of the decrease in infarct size and cardiac fibrosis, the attenuation of apoptosis in the myocardium, improvements in ventricular remodelling and inflammation …”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that exercise training, including exercise training before and after infarction, provides promising effects on the repair of the infarcted heart, regardless of the decrease in infarct size and cardiac fibrosis, the attenuation of apoptosis in the myocardium, improvements in ventricular remodelling and inflammation. [3][4][5][6][7][8][9][10] However, various studies in animals and humans have also shown conflicting results concerning the effects of exercise training, including neutral [11][12][13][14] and adverse [15][16][17] effects, on LV remodelling after MI.…”
Section: Introductionmentioning
confidence: 99%
“…19 Despite the cardio-protective effects of training, athletes are not exempted from acute coronary syndromes. However, the deleterious effects of MI seem to be reduced by lifelong exercise training, as shown in the study of Maessen et al 20 Thus physical training, protects not only against CV injury, but it also reduced the damage after injury.…”
Section: Physical Exercise As a Therapymentioning
confidence: 87%
“…Exercise training exerted beneficial effects in the process of cardiopulmonary rehabilitation and LV remodeling in the LV dysfunction patients after MI, and the greatest effects were achieved when exercise began at the post-MI acute phase (Zhang et al, 2016). A cross-sectional study of 65 men (60 ± 6 years) found that lifelong exercise training maintained LV systolic function and probably alleviated or minimized the detrimental effects of LV remodeling after MI in veteran athletes (Maessen et al, 2017). LV end diastolic and systolic volumes had significantly decreased in MI patients after 10 weeks of exercise training (Mc et al, 2016).…”
Section: The Benefits Of Exercise For MImentioning
confidence: 99%